Newly Diagnosed T1DM With Dka In Major β-Thalassemia Patient During Covid-19 Infection - Tri Hadmoko, Satrio; Ardiany, Deasy (Journal of Neonatal Surgery, 2025)
The COVID-19 pandemic has significantly impacted global public health, with diabetes mellitus (DM) being a key factor associated with adverse clinical outcomes. This case report discusses a 20-year-old male diagnosed with major β-thalassemia who developed newly diagnosed type 1 diabetes mellitus (T1DM) with diabetic ketoacidosis (DKA) during COVID-19 infection. Thalassemia patients are at increased risk for iron overload, which contributes to β-cell dysfunction and insulin resistance, leading to diabetes. This patient had persistent hyperglycemia, recurrent DKA, and was classified as idiopathic T1DM due to negative autoantibodies and low C-peptide levels. The case highlights the complex interplay between iron overload, β-cell dysfunction, and hyperglycemia in thalassemia patients, compounded by COVID-19 infection. Despite intensive management, including insulin therapy, fluid resuscitation, and iron chelation therapy, the patient succumbed to transfusion-related acute lung injury (TRALI). This case underscores the need for early detection of diabetes in thalassemia patients and emphasizes the importance of optimizing iron chelation therapy to reduce metabolic complications.